2017
DOI: 10.1186/s12906-017-2060-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-stress and neuronal cell differentiation induction effects of Rosmarinus officinalis L. essential oil

Abstract: BackgroundMood disorder accounts for 13 % of global disease burden. And while therapeutic agents are available, usually orally administered, most have unwanted side effects, and thus making the inhalation of essential oils (EOs) an attractive alternative therapy. Rosmarinus officinalis EO (ROEO), Mediterranean ROEO reported to improve cognition, mood, and memory, the effect on stress of which has not yet been determined. Here, the anti-stress effect of ROEO on stress was evaluated in vivo and in vitro.MethodsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 46 publications
2
17
0
2
Order By: Relevance
“…In this study, the application of 6-h restraint stress increased the CORT levels in rats while inhalation exposure to 1-MN at 50 mg/m 3 significantly reduced the stress. These results suggest that 1-MN interacts with the HPA axis similarly to many volatile compounds [3,11,[27][28][29][30][31]. The non-linear effect on the stress level, as observed in this study, was also reported for other organic solvents like 1,2,4-trimethylbenzene (pseudocumene [PS]) or 1,2,3-trimethylbenzene (hemimellitene [HM]) [32][33][34].…”
Section: Discussionsupporting
confidence: 82%
“…In this study, the application of 6-h restraint stress increased the CORT levels in rats while inhalation exposure to 1-MN at 50 mg/m 3 significantly reduced the stress. These results suggest that 1-MN interacts with the HPA axis similarly to many volatile compounds [3,11,[27][28][29][30][31]. The non-linear effect on the stress level, as observed in this study, was also reported for other organic solvents like 1,2,4-trimethylbenzene (pseudocumene [PS]) or 1,2,3-trimethylbenzene (hemimellitene [HM]) [32][33][34].…”
Section: Discussionsupporting
confidence: 82%
“…Similar enhancement of cognitive function was also found in the aroma of common sage (Salvia officinalis) and Spanish sage (Salvia lavandulifolia) [46]. In studies using mice, rosemary (Rosmarinus officinalis) suppressed serum corticosterone level, suggesting its anti-stress effect [47]. Further, 2-Phenylethanol, which is a main component of rose (Rosa) essential oil, decreased immobility time in a tail suspension test, suggesting its anti-depression effect, but it did not affect cognitive function, activity level, muscle strength, or aggression in mice [48].…”
Section: The Effects Of Essential Oils and Terpenes Through The Olfacmentioning
confidence: 54%
“…Este efeito estimulante pode estar relacionado aos compostos químicos presentes no óleo desta espécie, como o 1,8-cineol e cânfora que apresentam a capacidade de estimular a atividade do Sistema Nervoso Central (Hongratanaworakit et al, 2017;Kovar, Gropper, Friess, & Ammon, 1987). O efeito ansiolítico do óleo está relacionado ao α-pineno (Satou et al, 2018;Villareal et al, 2017). Research, Society and Development, v. 9, n. 9, e228996971, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.6971 índice comportamental da capacidade do animal de agir de acordo com estímulos ao estresse.…”
Section: Resultsunclassified